Pengaruh Lingkungan Sekolah Terhadap Semangat Belajar Siswa di SMA Swasta Budi Satrya Medan - Khalisatun Husna; Muhammad Chaidir; Abdul Fattah Nasution (PT PUBLIKASI INSPIRASI INDONESIA, 2026)
This study aims to determine the influence of the school environment on students' enthusiasm for learning. The study used a quantitative approach with a survey method of 32 students using a Likert-scale questionnaire. The school environment was measured through physical and social aspects, while enthusiasm for learning was measured through enthusiasm, persistence, participation, and responsibility for learning. The results showed that the school environment was categorized as good with an average score of 3.71, and student enthusiasm for learning was categorized as high with an average score of 3.78. However, the results of the correlation test indicated a weak relationship between the school environment and student enthusiasm for learning. This finding suggests that the school environment plays a supporting role, while student enthusiasm for learning is also influenced by factors other than the school environment.